Adaptive Governance and Integrated Water Resources Management in Argentina - Berardo, Ramiro; Meyer, Marcos; Olivier, Tomás (International Journal of Water Governance, 2013)
Since the early 2000s, international organizations and national and provincial authorities in Argentina have promoted a number of institutional initiatives to implement Integrated Water Resources Management in the country. The two main initiatives are the adoption of the Guiding Principles of Water Policy, and the ongoing design of the National Federal Plan of Water Resources. These are complemented by the creation of the Federal Water Council, a new nation-wide venue that gives the provincial and national governments the chance to engage in discussions related to the improvement of water management in the country. We analyze the process leading to the creation of this set of new institutions through the theoretical lens of Adaptive Governance, and assess how well national and provincial authorities have faced the challenges of representation (who participates in decision-making processes) and process design (how decisions are reached) that are so critical in the early stages of addressing interjurisdictional water problems. Drawing on in-depth interviews with decision-makers, we also identify other challenges to AG in Argentina, including the problem of discontinuation of policy efforts that could lead to a better implementation of IWRM principles, and the pervasive presence of personalismo in making decisions that affect water management.